2015
DOI: 10.14314/polimery.2015.219
|View full text |Cite
|
Sign up to set email alerts
|

Silsesquioxanes and their application in the synthesis of polymeric materials

Abstract: Artyku³ stanowi przegl¹d literatury dotycz¹cej syntezy oraz charakterystyki materia³ów polimerowych zawieraj¹cych silseskwioksany (POSS). Przedstawiono metody otrzymywania hybrydowych materia³ów polimerowych z udzia³em funkcjonalizowanych POSS na drodze click chemistry, polikondensacji, poliaddycji, metatezy z otwarciem pieroecienia i polimeryzacji rodnikowej zarówno konwencjonalnej, jak i kontrolowanej (ATRP).S³owa kluczowe: poliedryczne oligomeryczne silseskwioksany (POSS), materia³y hybrydowe, polikondensac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…Polyhedral oligomeric silsesquioxanes (POSSs) are hybrid organic–inorganic nanosized fillers and modifiers widely used for polymer modification . Numerous studies of the application of silsesquioxanes as NAs for iPP have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxanes (POSSs) are hybrid organic–inorganic nanosized fillers and modifiers widely used for polymer modification . Numerous studies of the application of silsesquioxanes as NAs for iPP have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…The most significant branch of SQs successful application is material chemistry as nanofillers and polymers modifiers [65][66][67][68][69][70][71]. Depending on the type of applied silsesquioxane and its amount in a polymer matrix, the resulting nanocomposite material possesses improved properties, i.e., mechanical (increased elongation at break, lower friction), optical (maintained optical transparency, reduced or removed the color of the nanocomposite), thermal (increased thermal resistance and glass transition temperature, lowered thermal conductivity), and others (e.g., improved the oxidation and corrosion resistance, reduced flammability of the material) [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. There are a few possibilities to introduce silsesquioxane molecules into the polymer matrix ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%